CONSUMERS HEALTH AND SAFETY ON THE INTERNET BASED MEDICAL CONSULTATION - Norma Sari (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
The rise of the internet-based medical consultation has opened not only opportunities for consumers easily obtaining medical services but also put them at risk for mistreatment, misunderstanding or taking a wrong medication to be anticipated. This research concerns on how the internet-based medical consultation affects to the health and safety of the consumers. There are several identified legal issues have to be paid attention as follow: (i) the benefit and shortcoming of using internet-based medical consultation, (ii) inter-related and overlapped interest of the parties, (iii) consumer health and safety, (iv) consumer rights, and (v) dispute settlement. Pertumbuhan konsultasi pengobatan berbasis internet telah membuka peluang tidak hanya bagi konsumen. Kemudahan mendapatkan pelayanan medis tetapi juga menempatkan mereka pada risiko kesalahan perawatan, kesalahpahaman atau kesalahan dalam pemberian obat sehingga hal ini harus diantisipasi. Penelitian ini menjelaskan mengenai konsultasi pengobatan berbasis internet yang mempengaruhi kesehatan dan keselamatan konsumen. Ada beberapa masalah hukum yang harus diperhatikan dan diidentifikasi menjadi sebagai berikut, yakni: (i) manfaat dan kelemahan menggunakan konsultasi pengobatan berbasis internet, (ii) hubungan dan tumpang tindih kepentingan para pihak, (iii) kesehatan dan keselamatan konsumen, (iv) hak-hak konsumen, dan (v) penyelesaian sengketa.